Communities of practice in the management of an Arctic environment: monitoring knowledge as complementary to scientific knowledge and the precautionary principle? - Nyseth, Torill; Viken, Arvid (Polar Record, 2015)
ABSTRACT This article addresses knowledge management in governing vulnerable polar areas and tourism. Since the 1870s, Svalbard has been a cruise tourism destination. Due to less ice during the summer period, the number of tourists visiting the remote northeast corner of the archipelago has increased significantly, and the potential negative impact on this vulnerable natural environment has become an issue. The standard modes of managing these areas have either been to apply the precautionary principle or measures based on scientific evidence. As management models, however, both principles are contested for a number of reasons. This paper argues for a third model that is partly based on a form of monitoring knowledge that has circulated in ‘communities of practice’ and that has been developed over time. This form of knowledge constitutes viable expertise for the governing and management of the environment-tourism nexus in the area, but it needs to be acknowledged as a complementary management platform. This article demonstrates how such monitoring can be done, and it suggests some principles for the development of monitoring knowledge for administrative and management purposes.